2016
DOI: 10.1039/c5lc00994d
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput mechanofluidic screening platform for investigating tumor cell adhesion during metastasis

Abstract: The metastatic spread of cancer is a major barrier to effective and curative therapies for cancer. During metastasis, tumor cells intravasate into the vascular system, survive in the shear forces and immunological environment of the circulation, and then extravasate into secondary tumor sites. Biophysical forces are potent regulators of cancer biology and are key in many of the steps of metastasis. In particular, the adhesion of circulating cells is highly dependent upon competing forces between cell adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…These included inhibitors to FLT-3, PI-3K, JAK3, EGFR and VEGFR. Consistent with our findings here, our previous study using the high throughput shear stress device also identified FLT-3 inhibitors to be effective in blocking cancer cell adhesion to endothelial cells under shear stress (15). The PI3K inhibitor reduced metastasis to the skull in immune compromised mice for the load conditioned cells, suggesting the strategy of screening for inhibitors of cancer cell to endothelial cell adhesion could be a means to identify therapeutics that protect against metastatic spread of cancer but that multiple pathway targeting may be needed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These included inhibitors to FLT-3, PI-3K, JAK3, EGFR and VEGFR. Consistent with our findings here, our previous study using the high throughput shear stress device also identified FLT-3 inhibitors to be effective in blocking cancer cell adhesion to endothelial cells under shear stress (15). The PI3K inhibitor reduced metastasis to the skull in immune compromised mice for the load conditioned cells, suggesting the strategy of screening for inhibitors of cancer cell to endothelial cell adhesion could be a means to identify therapeutics that protect against metastatic spread of cancer but that multiple pathway targeting may be needed.…”
Section: Discussionsupporting
confidence: 92%
“…In our past work, we developed a high throughput system for applying flow to cells cultured in 96 well plates (14)(15)(16). The device is composed of a rotational motor that drives a 96 gear box, simultaneously rotating 96 shafts with low angle cone tips, which interface with a standard format 96 well plate.…”
Section: High Throughput Cancer Cell Adhesion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that mechanical strain in the vascular microenvironments could accelerate tumor necrosis factor‐related apoptosis inducing ligand (TRAIL)‐induced apoptosis and regulate adhesion of tumor cells to the endothelium. The Baker group developed a high‐throughput mechanofluidic device to investigate the adhesion of tumor cells subjected to physiological shear stress . With the help of the proposed platform, the authors identified FLT‐3 and AKT inhibitors that impeded tumor cell adhesion to platelets and endothelial cells in the presence of fluid flow.…”
Section: Microfluidic Platforms For Engineered Tumor Microenvironmentmentioning
confidence: 99%
“…With the help of the proposed platform, the authors identified FLT‐3 and AKT inhibitors that impeded tumor cell adhesion to platelets and endothelial cells in the presence of fluid flow. Moreover, kinase inhibitors were observed to promote tumor cell adhesion in flow‐based, other than, static assays . Additionally, Garcia et al designed a robust microfluidic chip to establish stable orthogonal gradients of ECM stiffness and chemical concentration to study Madin–Darby canine kidney (MDCK) canine cell migration .…”
Section: Microfluidic Platforms For Engineered Tumor Microenvironmentmentioning
confidence: 99%